Hubungan Antara Religiusitas Dengan Kecemasan Akademik Pada Siswa Di MBS Prambanan Yogyakarta - Ramadani, Magfira; Aisah, Anita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Students often experience anxiety in academic situation. Excessive anxiety will interfere with students' concentration on academic things. If students have a high sense of religiosity, they will feel calm and can control anxiety over them. This study analyzed the relationship between religiosity and anxiety over academic things in science class XII students at MBS Prambanan Yogyakarta. This research is correlational research with quantitative approach. The sampling technique was random with 60 respondents. The data were obtained using measuring instrument of questionnaire with likert- scale. The data were analyzed with product moment correlation test. The hypothesis proposed was the relationship between religiosity and anxiety over academic things in students at MBS Prambanan Yogyakarta. The proposed hypothesis was accepted, with significance value of 0.00<0.05, and the product moment correlation test showed that there was a correlation between variable X and variable Y. The correlation value was -0.705 in which there was a strong degree of correlation between variable X and variable Y and the form of the relationship was negative which meant that the higher the religiosity, the lower the anxiety over academic things and vice versa, the lower the religiosity, the higher the anxiety over academic things in students at MBS Prambanan Yogyakarta. The results of the study showed that there was a relationship between religiosity and anxiety over academic things in students at MBS Prambanan Yogyakarta.